Utilizing big data paradigms for business intelligence - Darmont, Jérôme 1972-; Loudcher, Sabine (IGI Global, Disseminator of Knowledge, 2019)
"This book explores problems related to the five "Vs" of big data, technological issues, as well as big data analytics applications. It also covers how data must be extracted, grouped, organized, aggregated and correlated with methods and techniques such as data integration (ETL), data warehousing, online analytical processing (OLAP), reporting, data mining and machine learning"...
Includes index
Keywords: Business intelligence -- Data processing; Big data; Aufsatzsammlung